2016
DOI: 10.1097/md.0000000000003033
|View full text |Cite
|
Sign up to set email alerts
|

Histiocytoid Sweet Syndrome Is More Frequently Associated With Myelodysplastic Syndromes Than the Classical Neutrophilic Variant

Abstract: Histiocytoid Sweet syndrome (H-SS) is a histological variant of Sweet syndrome (SS) differing from classical neutrophilic SS (N-SS) by a dermal infiltrate mainly composed of lymphocytes and histiocytoid myeloperoxidase-positive cells. We aimed to report a large series of H-SS and compare the frequency and type of hematological malignancies associated to H-SS and N-SS. We included 62 patients with a coding histopathologic diagnosis of SS prospectively registered between 2005 and 2014 in the database of our Depa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 41 publications
5
52
2
3
Order By: Relevance
“…There have also been several histologic variations reported in the literature. Jordaan reported variations in the cellular infiltrate, including lymphocytes, and years later, lymphocyte‐rich and histiocytoid lesions of SS were linked with myelodysplastic syndrome (MDS) . Similar to Jordaan's report, we have observed a consistent presence of lymphocytes in lesions of SS, in patients who do not have associated hematologic disorders.…”
Section: Introductionsupporting
confidence: 86%
“…There have also been several histologic variations reported in the literature. Jordaan reported variations in the cellular infiltrate, including lymphocytes, and years later, lymphocyte‐rich and histiocytoid lesions of SS were linked with myelodysplastic syndrome (MDS) . Similar to Jordaan's report, we have observed a consistent presence of lymphocytes in lesions of SS, in patients who do not have associated hematologic disorders.…”
Section: Introductionsupporting
confidence: 86%
“…Our case demonstrates the importance of performing a complete blood count (CBC) at the time of diagnosis of HSS followed by thorough hematological evaluation should a cytopenia be detected. This case also supports a role for continued CBC monitoring in HSS as often, cutaneous HSS lesions may precede the diagnosis of hematologic malignancy …”
Section: Discussionsupporting
confidence: 69%
“…They concluded that the incidence of hematologic malignancies in HSS cases is comparable to that among classical SS cases, which is estimated at 18% . Other studies have described a possible unique association between HSS and MDS, with one case series reporting MDS in 5/13 (38%) HSS cases and another reporting MDS in 7/22 (31.8%) HSS cases . Fluorescence in situ hybridization (FISH) has been used to identify cytogenetic abnormalities occurring in cases of HSS associated with AML/MDS …”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective study showed the histiocytoid or subcutaneous variants exclusively in the setting of malignancy (14). Several studies have also suggested the relationship of histiocytoid or subcutaneous Sweet syndrome with hematologic disorders (16)(17)(18)(19). However, our cases did not show statistically significant differences in histopathology between the patients with and without hematologic malignancy.…”
Section: Aml* Comparison Of Hemoglobin and Platelet Levels Between Scontrasting
confidence: 72%